If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3d + 13 + -6 + -13.20 = 2.07 Reorder the terms: 13 + -6 + -13.20 + 3d = 2.07 Combine like terms: 13 + -6 = 7 7 + -13.20 + 3d = 2.07 Combine like terms: 7 + -13.20 = -6.2 -6.2 + 3d = 2.07 Solving -6.2 + 3d = 2.07 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '6.2' to each side of the equation. -6.2 + 6.2 + 3d = 2.07 + 6.2 Combine like terms: -6.2 + 6.2 = 0.0 0.0 + 3d = 2.07 + 6.2 3d = 2.07 + 6.2 Combine like terms: 2.07 + 6.2 = 8.27 3d = 8.27 Divide each side by '3'. d = 2.756666667 Simplifying d = 2.756666667
| X=28+14 | | 6=1.2 | | s-3.2=6 | | X=19+13 | | X=25+17 | | 12.3=14-b | | t+13=3 | | 8t^2+17t-25=0 | | X=18-11 | | f(x)=4x^2+8x+11 | | 7.09=3+y | | -6n+48=6u | | 1+12= | | -7x-2(11+2y)=-13 | | 0.2x-1.8=-4.2 | | 672-3x=448-2x | | x-4*3=5 | | m=3-7 | | 10x+110=12x+96 | | 11*3x=20 | | 11*3x=17 | | 11*3x=2 | | 708=n+300 | | 9(x+8)=5[x-(8-x)] | | 1.2y-12=-2.8y-25.2 | | x=24+15 | | n-305=225 | | -3x+5x-4x=13 | | 6h-11-h=4-37h-2 | | 6h-11-h=4-37h-3 | | 5x-8=4x+3(x+1) | | 4-3x=274 |